Denotative and connotative analysis on Elia Pettie’s short story - Nur Nabilah Fauziyah; Roikhatul Nur Ilmi (Politeknik Negeri Bali, 2020)
This study was conducted to analyze several words which have denotative and connotative meaning and find the relation of those words with the context of a love relationship in real life. In analyzing the denotative and connotative meaning of four words that were already chosen, this study uses Palmer’s theory of denotation and connotation as a theoretical basis. The data was collected from the text of the short story “A Child of the Rain”, which is categorized as a ghost story. Particularly, this study focuses on analyzing four specific words namely invisible, glad, expert, and coldness. This study uses descriptive qualitative as the design of this study. Therefore, after analyzing the meaning of words, this study found that (1) the words invisible, glad, expert, and coldness have denotative and connotative meaning, (2) connotative meaning of these words have a relation with the context of love relationship in real life, (3) these words can portray someone’s feeling in specific situation like in love relationship. These findings can be utilized by second-language learners in the process of understanding the denotative and connotative meaning of the English language.